Tindak Pidana Perdagangan Orang (Human Trafficking) Studi Kasus Putusan Nomor 2207/PID.SUS/2022/PN.MDN - Zulwanda, Defri Tri; Ningrum, Maya Puspita (Sekolah Tinggi Ilmu Hukum Graha Kirana, 2022)
Abstract Women have the same rights as men to obtain guarantees for fulfilling the right to live a decent, healthy and dignified life. Therefore, the state, especially the government, is responsible for the promotion, protection and fulfillment (to promote, to protect, to fulfill) these rights, as an integral part of fulfilling human rights. A number of laws and regulations have been created by the Indonesian government related to labor migration, human trafficking and HIV/AIDS. The hope is that this legislation will be able to provide protection for the Indonesian state, both men and women. However, two facts show that these laws and regulations are not very effective in protecting the community, especially women. One form of crime of trafficking in persons, especially women and children, which is widely practiced as a crime with a cross-regional dimension within countries and across countries (transnational organization crime) is trafficking in persons for the purpose of sexual exploitation or prostitution. The mode of operation of the crime of trafficking in persons for the purpose of sexual exploitation has become increasingly complex over time and increasingly difficult to prosecute. The victims are also increasing in terms of number and situation of victims, namely from adult women to girls, even children under the age of 10 are trapped in the ijok system carried out by criminals who traffic in people with their parents. The aim of this research is to answer problems related to the application of material criminal law to criminal acts of human trafficking (Human Trafficking) case study number 2207/pid.sus/2022/PN.Mdn and to find out the legal considerations of judges in imposing criminal sanctions against perpetrators of criminal acts of trafficking people (Human Trafficking) in decision 2207/pid.sus/2022/PN. Mdn The research used to answer the two things above is library research and taking data obtained from court decisions at the Medan District Court. The results of this research indicate that the application of material criminal law to the criminal act of human trafficking in the judge's decision in case no. 2207/PID.SUS/2022/PN.MDN. In accordance with the law, in this case it is regulated in Law number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. In handing down criminal sentences, the judge has given considerations in accordance with the facts and those revealed in court, both in terms of material criminal and formal criminal considerations.Key words: Crime, crime, human traffickingAbstrak Perempuan memiliki hak yang sama dengan laki-laki untuk memperoleh jaminan atas pemenuhan hak untuk hidup layak, sehat dan bermartabat. Oleh sebab itu, negara, terutama pemerintah bertanggung jawab atas promosi, perlindungan dan pemenuhan (to promte, to protect,to fulfill) hak-hak tersebut, sebagai bagian yang terpisahkan dari pemenuhan hak asasi manusia. Sejumlah peraturan perundangan telah di ciptakan oleh pemerintah Indonesia terkait dengan migrasi tenaga kerja, perdagangan orang dan hiv/aids. Harapannya, peraturan Perundangan ini mampu memberikan perlindungan bagi negara Indonesia, laki-laki maupun perempuan. Namun dua kenyataan menunjukkan bahwa peraturan perundangan tersebut tidak terlalu efektif melindungi masyarakat, terutama perempuan. Salah satu bentuk kejahatan perdagangan orang, khususnya perempuan dan anak yang banyak di praktikkan sebagai kejahatan berdimensi lintas wilayah dalam negara maupun lintas negara (transnational organise crime) adalah perdagangan orang untuk tujuan exploitasi seksual atau pelacuran. Modus operasi kejahatan perdagangan orang untuk tujuan exploitasi seksual ini dari waktu ke waktu semakin komplek dan semakin sulit dijerat hukum. Korbannya pun semakin meningkat dari sisi jumlah maupun situasi korban, yaitu dari perempuan usia dewasa hingga anak perempuan, bahkan anak anak masih di bawah usia 10 tahun terjebak sistem ijok yang di lakukan oleh para penjahat perdagangan orang dengan orang tua mereka. Tujuan penelitian ini adalah untuk menjawab permasalahan terkait penerapan hukum pidana materil terhadap tindak pidana perdagangan orang (Human Trafficking) studi kasus nomor 2207/pid.sus/2022/PN.Mdn dan untuk mengetahui pertimbangan hukum hakim dalam menjatuhkan sanksi pidana terhadap pelaku tindak pidana perdagangan orang (Human Trafficking) dalam putusan 2207/pid.sus/2022/PN. Mdn Penelitian yang digunakan untuk menjawab dua hal diatas adalah penelitian kepustakaan dan mengambil data yang diperoleh dari putusan pengadilan di Pengadilan Negeri Medan. Dari hasil penelitian ini menunjukkan bahwa penerapan hukum pidana materil terhadap tindak pidana perdagangan orang (Human Trafficking) dalam putusan hakim dalam perkara No. 2207/PID.SUS/2022/PN.MDN. Telah sesuai dengan perundangundangan dalam hal ini diatur dalam Undang-undang nomor 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang dalam menjatuhkan vonis pidana hakim telah memberikan pertimbangan-pertimbangan sesuai dengan fakta dan terungkap dipersidangan baik itu dari pertimbangan segi pidana materil maupun dari pidana formil